SOME POINTS IN THE HISTORY OF THE TEXTUS RECEPTUS OF THE NEW TESTAMENT - Nestle, Eb (The journal of theological studies, 1910)
EB. NESTLE; SOME POINTS IN THE HISTORY OF THE TEXTUS RECEPTUS OF THE NEW TESTAMENT, The Journal of Theological Studies, Volume os-XI, Issue 4, 1 July 1910, Page